A refined finite element analysis on the vibrational properties of ideal and degenerated carbon nanostructures. (April 2016) - Imani Yengejeh, Sadegh; Kazemi, Seyedeh Alieh; Ivasenko, Oleksandr; Öchsner, Andreas
Abstract: Different types of degenerated nanostructures were simulated and their eigenfrequencies and corresponding eigenmodes were evaluated by applying the well-established finite element method. In addition, the structural and vibrational stability of these nanoparticles was examined under the influence of microscopic modifications. For this purpose, four common types of atomic defects (i.e. different types of vacancy defects, perturbation, pentagon–heptagon pair defect and chemical doping) were introduced to the finite element models and their vibrational properties were obtained and finally compared to those of perfect, i.e. defect-free, structures. The detailed geometry around a defected area was calculated based on density functional theory and implemented in the finite element model. Based on the results, it was shown that all these structural modifications changes the natural frequency and as a result, reduce the vibrational stability of degenerated nano-materials. Graphical abstract: Highlights: Degenerated nanostructures were numerically simulated. Different types of microscopic defects were introduced to the models. The natural frequency of defect free and modified models were obtained. Atomic defects reduce the vibrational stability of the nanostructures.